Hydraulic modeling : concepts and practice - Ettema, R. (ASCE manuals and reports on engineering practice, 2000)
Prepared by the Task Committee on Hydraulic Modeling of the Environmental and Water Resources Institute of ASCE. Hydraulic Modeling presents the ideas behind model design and use for a broad spectrum of hydraulic modeling methods. Detailed guidance is provided for selecting the modeling approach most likely to produce the data sought. This Manual, which updates an earlier edition, provides many different methods of hydraulic modeling from which to choose by covering an extensive assortment of modeling topics, technical issues, and strategies. This revised Manual reflects significant advances in modeling methods and the broadening of hydraulic issues addressed by means of hydraulic modeling. Topics include: Similitude and dimensional analysis; Single-phase flow; Loose boundary flow; Gas-liquid flows; Environmental flows; Coastal and estuary processes; Ice, debris, and hydroelastic vibrations; Hydraulic machinery; Design, construction, and operation of hydraulic models; and Instrumentation and data acquisition. Five case studies provide an overall sense of the modeling process from start to finish.